Teaching a foreign language to young economists in Ukraine in cross-cultural communication environment - Kovalova, Olena; Kovalska, Nataliia (My University, 2019)
Due to the tendency to globalisation, economists all over the world have a strong necessity to master a foreign language. Young generation of future economists needs innovative approaches to language teaching. This article reveals the results of the research into methodological and psychological aspects of teaching a foreign language to students of economic departments in Ukraine and states the essential educational objectives. It also suggests a novel teaching framework whose major goal is to give an advantage to students in their overcoming language, communication and cross-cultural barriers in studying process and which can be regarded as highly integral to the objectives. Через схильність до глобалізації економісти в усьому світі гостро потребують оволодіння іноземною мовою. Молодому поколінню майбутніх економістів потрібні інноваційні підходи до викладання мови. У цій статті розкриваються результати досліджень методологічних та психологічних аспектів навчання іноземної мови студентам економічних факультетів України та окреслюються найважливіші навчальні цілі. Він також пропонує нові навчальні рамки, основна мета яких - надати перевагу студентам у подоланні мовних, комунікаційних та міжкультурних бар'єрів у навчальному процесі, які можна розглядати як дуже невід'ємну частину цілей.
Keywords: міжкультурна комунікація; cross-cultural communication; learning a foreign language; кафедра ділової іноземної мови та міжнародної комунікації; вивчення іноземної мови